2019
DOI: 10.1080/20013078.2019.1656993
|View full text |Cite
|
Sign up to set email alerts
|

DNA analysis of low‐ and high‐density fractions defines heterogeneous subpopulations of small extracellular vesicles based on their DNA cargo and topology

Abstract: 2019) DNA analysis of low-and high-density fractions defines heterogeneous subpopulations of small extracellular vesicles based on their DNA cargo and topologyABSTRACT Extracellular vesicles have the capacity to transfer lipids, proteins, and nucleic acids between cells, thereby influencing the recipient cell's phenotype. While the role of RNAs in EVs has been extensively studied, the function of DNA remains elusive. Here, we distinguished novel heterogeneous subpopulations of small extracellular vesicles (sEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
161
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(173 citation statements)
references
References 45 publications
9
161
3
Order By: Relevance
“…[10][11][12] Nevertheless, the proportion of ctDNA engulfed into extracellular vesicles actively released by tumour cells is still unclear and the effect of different therapy regimens on this active secretion mostly unknown. 13,14 Obviously, there is a huge need for more fundamental research on the kinetics of ctDNA in cancer patients.…”
mentioning
confidence: 99%
“…[10][11][12] Nevertheless, the proportion of ctDNA engulfed into extracellular vesicles actively released by tumour cells is still unclear and the effect of different therapy regimens on this active secretion mostly unknown. 13,14 Obviously, there is a huge need for more fundamental research on the kinetics of ctDNA in cancer patients.…”
mentioning
confidence: 99%
“…It has been demonstrated that exosomes can transfer specific proteins, nucleic acids, and lipids from donor cells to recipient cells, thereby influencing the phenotype of the recipient cells (Milane et al, 2015;Ruivo et al, 2017;Wan et al, 2018;Lazaro-Ibanez et al, 2019). Recent studies found that tumor-derived exosomes can transport PD-L1 from PD-L1-positive tumor cells to PD-L1-negative tumor cells (Yang et al, 2018).…”
Section: Exopd-l1 Interacts With Pd-1 On T Cells After Migration To Pmentioning
confidence: 99%
“…A study characterized subpopulations within the EV population with different DNA and RNA content and topology. In addition, they identified two types of DNAs, internally protected and external surface-related DNA, that could be used as a basis for developing diagnostic methods [68,69].…”
Section: Extracellular Vesicles As Ideal Cancer Biomarkersmentioning
confidence: 99%